The spectrum of involuntary vocalizations in humans: A video atlas. Issue 12 (25th October 2019) - Mainka, Tina; Balint, Bettina; Gövert, Felix; Kurvits, Lille; van Riesen, Christoph; Kühn, Andrea A.; Tijssen, Marina A.J.; Lees, Andrew J.; Müller‐Vahl, Kirsten; Bhatia, Kailash P.; Ganos, Christos
Abstract: In clinical practice, involuntary vocalizing behaviors are typically associated with Tourette syndrome and other tic disorders. However, they may also be encountered throughout the entire tenor of neuropsychiatry, movement disorders, and neurodevelopmental syndromes. Importantly, involuntary vocalizing behaviors may often constitute a predominant clinical sign, and, therefore, their early recognition and appropriate classification are necessary to guide diagnosis and treatment. Clinical literature and video‐documented cases on the topic are surprisingly scarce. Here, we pooled data from 5 expert centers of movement disorders, with instructive video material to cover the entire range of involuntary vocalizations in humans. Medical literature was also reviewed to document the range of possible etiologies associated with the different types of vocalizing behaviors and to explore treatment options. We propose a phenomenological classification of involuntary vocalizations within different categorical domains, including (1) tics and tic‐like vocalizations, (2) vocalizations as part of stereotypies, (3) vocalizations as part of dystonia or chorea, (4) continuous vocalizing behaviors such as groaning or grunting, (5) pathological laughter and crying, (6) vocalizations resembling physiological reflexes, and (7) other vocalizations, for example, those associated with exaggerated startle responses, as part of epilepsy and sleep‐related phenomena. We provide comprehensive lists of their associated etiologies, including neurodevelopmental, neurodegenerative, neuroimmunological, and structural causes and clinical clues. We then expand on the pathophysiology of the different vocalizing behaviors and comment on available treatment options. Finally, we present an algorithmic approach that covers the wide range of involuntary vocalizations in humans, with the ultimate goal of improving diagnostic accuracy and guiding appropriate treatment. © 2019 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.